Financial Services Authority Intervention as an Effort to Protect Bondholders in Corporations Declared Bankrupt by Commercial Court - Happy Permata Sari; Joni Emirzon; Saleh, Putu Samawati (Fakultas Hukum Universitas Muhammadiyah Sorong, 2025)
This article discusses the fulfillment of rights for corporate bondholders declared bankrupt by the Commercial Court. No regulation can provide a comprehensive and integrated benchmark to ensure the protection of the rights of bondholder creditors, making this article important to discuss. This research aims to analyze the status of corporate bondholders declared bankrupt by the Commercial Court as creditors in the liquidation process, evaluate the forms of legal protection applied during the process, and assess the future application of the law in providing certainty of protection for bondholders. This research used normative legal research with statutory, historical, and futuristic approaches. The discussion results are carried out using an analysis perspective emphasizing deductive conclusions. Although corporate bondholders declared bankrupt by the Commercial Court have rights as creditors in the bankruptcy process, the legal protection is still ineffective. A regulatory gap results in uncertainty when implementing protection for bondholders. Revision of the Bankruptcy Law by including regulations regarding bondholders' creditors will provide certainty for the protection of creditors' rights, which can be derived in the Financial Services Authority (OJK) Regulation by enforcing supervision in the bankruptcy process in order to protect the interests of bondholders and ensure the stability of the economic development.